Artificial boundary conditions for the ILES modeling of plane channel flow using the Cabaret scheme - Asfandiyarov, D.G. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2019)
Some results of ILES modeling of the plane channel flow of a viscous incompressible fluid using the Cabaret scheme are discussed. The possibility of modifying the calculation of flow near the wall is considered to determine the average characteristics more accurately. The "artificial" boundary conditions are introduced by using a special eddy viscosity model in the first layer of cells near the wall to correctly account for shear effects. The results of numerical simulation of plane channel flow obtained using the Cabaret scheme with and without artificial boundary conditions are compared in a wide range of Reynolds numbers. It is shown that the introduced modifications in the near-wall layer improve the accuracy of determining the average flow characteristics, especially the second moments. The obtained data are also compared with the results of LES modeling by the pseudospectral method and with the data from direct numerical simulation.